Inhibition of a Mitotic Motor Compromises the Formation of Dendrite-like Processes from Neuroblastoma Cells - Yu, Wenqian (The Rockefeller University Press, 1997)
Microtubules in the axon are uniformly oriented, while microtubules in the dendrite are nonuniformly oriented. We have proposed that these distinct microtubule polarity patterns may arise from a redistribution of molecular motor proteins previously used for mitosis of the developing neuroblast. To address this issue, we performed studies on neuroblastoma cells that undergo mitosis but also generate short processes during interphase. Some of these processes are similar to axons with regard to their morphology and microtubule polarity pattern, while others are similar to dendrites. Treatment with cAMP or retinoic acid inhibits cell division, with the former promoting the development of the axon-like processes and the latter promoting the development of the dendrite-like processes. During mitosis, the kinesin-related motor termed CHO1/MKLP1 is localized within the spindle midzone where it is thought to transport microtubules of opposite orientation relative to one another. During process formation, CHO1/ MKLP1 becomes concentrated within the dendrite-like processes but is excluded from the axon-like processes. The levels of CHO1/MKLP1 increase in the presence of retinoic acid but decrease in the presence of cAMP, consistent with a role for the protein in dendritic differentiation. Moreover, treatment of the cultures with antisense oligonucleotides to CHO1/MKLP1 compromises the formation of the dendrite-like processes. We speculate that a redistribution of CHO1/MKLP1 is required for the formation of dendrite-like processes, presumably by establishing their characteristic nonuniform microtubule polarity pattern.